Abū al-Barakāt al-Bagdādī wa al-Salafiyyah Ibn Taimiyyah Anmūżajā - Mustafa, Awara Ali (Study Program of Arabic Language Teaching, 2024)
Our purpose of this study is to demonstrate the extent of his influence on the Sheikh of Salafism, Ibn Taymiyyah al-Harrani, as Ibn Taymiyyah is considered one of the most prominent figures influenced by the philosophy of Abu al-Barakat al-Baghdadi. Al-Baghdadi left a great impact on the Salafi approach in general and on Ibn Taymiyyah in particular. Our method in this study is to present the issues in which Ibn Taymiyyah was influenced by Abu al-Barakat al-Baghdadi, citing the texts contained in his books, while mentioning the texts in which he praised al-Baghdadi. One of the results of this study was that Ibn Taymiyyah admired Al-Baghdadi’s philosophical approach, attached great importance to his philosophy, and defended him strongly in his writings. He also often showered him with praise and great titles, despite the fact that Ibn Taymiyyah criticized Al-Baghdadi on some issues. Especially in the divine.